2013
DOI: 10.1007/s11248-012-9685-0
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 1 promotes hepatic lipid accumulation and lipotoxicity through the induction of SREBP-1c expression in zebrafish

Abstract: The activated cannabinoid receptor 1 (CB1R) is exclusively responsible for food intake and weight gain and regulates several pathological features associated with obesity in mammals. However, the precise role of CB1R in non-mammalian model systems is poorly understood. To investigate the functions of CB1R in zebrafish liver, we conditionally expressed CB1R proteins using a liver-specific Tet(off) transgenic system. In this study, we found hepatic lipid accumulation in CB1R transgenic zebrafish (CB) without dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Srebfs promote fatty acid and cholesterol uptake and synthesis and can act downstream of EC signaling in the liver, with levels that can be regulated in zebrafish and mice by administration of the EC anandamide (Migliarini and Carnevali, 2008;Pai et al, 2013). In mice, modulation of dietary methionine can alter Srebf expression by feedback induction (Aissa et al, 2014).…”
Section: Ec Signaling Regulates Methionine Metabolism Via Srebfsmentioning
confidence: 99%
“…Srebfs promote fatty acid and cholesterol uptake and synthesis and can act downstream of EC signaling in the liver, with levels that can be regulated in zebrafish and mice by administration of the EC anandamide (Migliarini and Carnevali, 2008;Pai et al, 2013). In mice, modulation of dietary methionine can alter Srebf expression by feedback induction (Aissa et al, 2014).…”
Section: Ec Signaling Regulates Methionine Metabolism Via Srebfsmentioning
confidence: 99%
“…A role for the cannabinoid receptor CB1 in obesity and energy homeostasis has been established in relation to food intake and energy balance (25,26). Activation of the CB1 receptor centrally and peripherally leads to altered energy balance and weight gain in model organisms (19,(27)(28)(29). Selective blockade of CB1 with rimonabant in human clinical trials demonstrated an effect on weight loss (30,31), but further evaluation of cardiovascular outcomes was limited by psychiatric side effects, including an apparent increase in suicide risk (32).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that CB signaling in the peripheral tissues of zebrafish has a role in metabolic-regulation that is conserved with rodents (Osei-Hyiaman et al, 2005b). To further examine this potential role, a transgenic line was recently developed to study the effects of hepatic cnr1 overexpression (Pai et al, 2013). Overexpression of cnr1 in the liver resulted in elevated hepatic expression of SREBP-1c, a transcription factor involved in lipogenesis, as well as a host of genes involved with the synthesis, transport, and storage of fatty acids.…”
Section: Zebrafish Ecb Gene Functionmentioning
confidence: 99%